Clay Supported TiO2 Nanocomposites for Photocatalytic Degradation of Volatile Organic Compounds (VOCs) and Dyes - Mishra, Amit (My University, 2019)
The TiO2/bentonite nanocomposites were synthesized by a simple, facile and less time consuming microwave heating method carried out at 180oC for 10 minutes. Formation of TiO2 nanoparticles on bentonite clay surface was confirmed by HRTEM with size in the range 10-20 nm. The as-obtained nanocomposites had better porosity, surface area (112 m2/g) compared to pure clays (7-20 m2/g) and commercial TiO2 (Degussa P25, Germany) (50 m2/g) which led to degradation of methylene blue dye in almost 60 minutes. TiO2/bentonite was further compared with TiO2/kunipia-F and TiO2/kaolin which were prepared under same conditions regarding photocatalytic MB and chlorobenzene degradation. The textural differences (1:1 and 2:1) between bentonite, kunipia-F and kaolin clays led to the variation in photoactivity of TiO2/clay nanocomposites. The photocatalytic activities of the nanocomposites were found to be depended on clay texture as well as optical features of clays apart from surface area. The 2:1 clays (bentonite, kunipia-F) were observed to be better support materials for TiO2 in comparison with 1:1 clay (kaolin) regarding photocatalytic degradation of methylene blue (MB) and chlorobenzene. Among the TiO2/clay nanocomposites TiO2/bentonite showed better photocatalytic activity for both MB and chlorobenzene degradation due to its high surface area and optical absorption. Different nobel metal NPs (Ag, Au, Pd, all 1% by wt.) were loaded on bentonite/TiO2 to form bentonite/M-TiO2 (M- Ag, Au and Pd) nanocomposites to study their effect on its photocatalytic activity under UV and visible light. Among the bentonite/M-TiO2 nanocomposites, bentonite/Ag-TiO2 showed the highest activity for benzaldehyde and chlorobenzene degradation under UV and visible light. Under visible light irradiation, the photocatalytic activity of bentonite/M-TiO2 was due to SPR effect of noble metal NPs, deposited on the bentonite/TiO2 surface in which the electron gets transferred to the conduction band of TiO2 from metal NPs surface. TiO2/bentonite nanocomposite was coupled with visible light active graphitic carbon nitride (g-C3N¬4) by wet impregnation process at room temperature. TiO2 nanoparticles were found to be in close proximity with g-C3N¬4 as observed from HRTEM. The g-C3N4/TiO2/bentonite nanocomposites showed better photocatalytic activity than pure g-C3N4 and g-C3N4 /bentonite due to very effective charge separation. The as-prepared nanocomposite effectively degraded (90%) reactive brilliant red dye (RBR- X3BS) in 100 minutes of time under visible light irradiation. The high activity was attributed to effective charge separation in the nanocomposite.
Ph D Thesis
Keywords: Clay; TiO2; VOC's; Dyes; Photocatalysis